Ethnography of the Ek-Static Experience: Poésie Auto-socioanalytique in the Work of Michel Leiris. (June 2015) - Riley, Alexander
Much work has been done in recent decades to emphasize the need in ethnographic writing to grapple with questions of authorship, perspective, aesthetics, emotional resonance, and style. Various forms of reflexive ethnographic writing, and especially autoethnography, have opened up new expressive avenues. In this article, I argue that a figure who is at present poorly known in English-language social scientific circles, the French ethnographer, poet, and writer Michel Leiris (1901–1990), pushes this kind of autobiographical ethnographic writing forward in powerful ways. In brief, Leiris offers a powerfully effective method (which I call poésie auto-socioanalytique ) that ties subjective experience into a larger objective structural framework via a method that (1) focuses on cultural meaning in an autobiographical experiential framework, that is, from the inside, (2) is expressly concerned with the role that language itself plays in meaning and memory, and (3) examines extraordinary situations in which one stands, temporarily, outside the normal interactional world in an existential frame of peculiar intensity and effervescence (the ek-static), and uses the Durkheimian conception of the sacred–profane opposition, along with the binary differentiation of the sacred into pure and impure varieties, as a structural theoretical tool for these descriptions. He makes an important contribution to ongoing discussions in the disciplines of cultural anthropology and cultural sociology concerning the interpretation and description of cultural meaning.